TLR9 signalling inhibits Plasmodium liver infection by macrophage activation. Issue 2 (27th November 2021) - Kordes, Maximilian; Ormond, Louise; Rausch, Sebastian; Matuschewski, Kai; Hafalla, Julius Clemence R.
Abstract: Recognition of pathogen‐associated molecular patterns (PAMPs) through Toll‐like receptors (TLRs) plays a pivotal role in first‐line pathogen defense. TLRs are also likely triggered during a Plasmodium infection in vivo by parasite‐derived components. However, the contribution of innate responses to liver infection and to the subsequent clinical outcome of a blood infection is not well understood. To assess the potential effects of enhanced TLR‐signalling on Plasmodium infection, we systematically examined the effect of agonist‐primed immune responses to sporozoite inoculation in the P. berghei /C57Bl/6 murine malaria model. We could identify distinct stage‐specific effects on the course of infection after stimulation with two out of four TLR‐ligands tested. Priming with a TLR9 agonist induced killing of pre‐erythrocytic stages in the liver that depended on macrophages and the expression of inducible nitric oxide synthase (iNOS). These factors have previously not been recognized as antigen‐independent effector mechanisms against Plasmodium liver stages. Priming with TLR4 and ‐9 agonists also translated into blood stage‐specific protection against experimental cerebral malaria (ECM). These insights are relevant to the activation of TLR signalling pathways by adjuvant systems of antimalaria vaccine strategies. The protective role of TLR4‐activation against ECM might also explain some unexpected clinical effects observed with pre‐erythrocytic vaccine approaches. Abstract : We evaluated the impact of enhanced TLR‐signalling on sporozoite‐induced Plasmodium infection. TLR9 signalling inhibited the development of pre‐erythrocytic stages in the liver that is dependent on pro‐inflammatory cytokines and effector mononuclear phagocytes/macrophages. TLR4 and ‐9 signalling translated into blood stage‐specific protection against experimental cerebral malaria.